Psychological prevention of injuries of the musculoskeletal system in elite athletes - E. I. Razumets (National Electronic Information Consortium (NEICON), 2021)
The article presents a study of traumatic experiences by high-class athletes (members of the Russian national teams). Data on the subjective sensations of athletes who have suffered from injury of the musculoskeletal system are obtained, patterns in the perception of the consequences of an injury event are revealed. Also we present data on the attitude of athletes to injury in the aspect of professional activity. The analyzed information is an important component in the development of personalized programs for the prevention of reinjury in elite sports.Objective: to assess the psychoemotional experiences of sports trauma by elite athletes in the process of rehabilitation treatment after the musculoskeletal system injury.Materials and methods: a specially developed medical and psychological interview was conducted with athletes-members of the sports national Russian Federation teams, who are inpatient treatment in the sports traumatology department, in order to obtain primary subjective information from the athlete about his presentation of his own experiences of a traumatic episode. Further, the information obtained from the interviews was analyzed and grouped for further evaluation.Results: we state the significant influence exerted by the previous traumatic experience on the future life and professional activity of an athlete. Moreover, the influence can be both negative (fear, anxiety, kinesiophobia, uncertainty in sports-specific movements) and positive (acquired skills of coping with traumatic experiences, gaining new knowledge about one's physical and psychological capabilities).Conclusions: thus, despite the diversity of individual reactions of athletes to injury, different life situations, sports and traumatic events, it is possible to identify general patterns in the perception of elite athletes of the injury itself, as well as the entire process of recovery and return to sports. This information is very important both for minimizing the negative impact of a sports injury on the psychological recovery of an athlete by switching his attention to identifying the "positive" consequences of the injury, and for the prevention of repeated injuries in elite sports.